ANALISIS STRATEGI PEMASARAN YANG DILARANG SYARI’AT PERSPEKTIF AL-IMAM MUHYIDDIN AN-NAWAWI - Kholit Al Asror , Mahdum; Hasani , Dahrul (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
The marketing strategy that is prohibited by the Shari'ah is an important discussion to study, because currently the competition in the world of trade is getting tighter and the strategies are also very varied, while without a new study on the discussion, it is feared that the innovations of marketers will come out of the guidance of the Shari'ah. at, this is none other than because marketers do not understand the theory of fiqh which is mostly in Arabic. This paper focuses on looking at the prohibited marketing strategies from the point of view of al-Imam Muhyiddin an-Nawawi, because the majority of Indonesian Muslims belong to the as-Syafi'i school of thought while al-Imam Muhyiddin an-Nawawi is an as-Syafi'i follower who has the most superior opinion. According to al-Imam Muhyiddin an-Nawawi, there are two marketing strategies that are prohibited by sharia, namely an-najasy and at-tadlis. An-najasy is a marketing strategy in the form of promotion where traders create fake customers to bid at a high price, with the aim of persuading buyers to be interested in the product being marketed even at a high price. While at-tadlis is a marketing strategy in the form of a product where the seller hides the defects of an item, by putting it on the inside or choosing a better product for the part that is shown. The marketing of an-najasy and at-tadlis is illegal because there is an element of fraud in it, but the contract that occurs is legal. According to the Syafi'iyyah scholars who are supported by Imam Nawawi, the consequences of an-najasy that occur due to collusion from the seller, there are two legal opinions: First, the buyer has the right of khiyar. Second, the buyer has no khiyar rights. Meanwhile, as a consequence of at-tadlis, the buyer still has khiyar rights.